Observations militaires - Espinay de Saint-Luc, François d', -1597.
A portion of Observations Militaires.
Negative photocopy.
French army officer.
Collection material in French.
Forms part of : Miscellaneous Manuscripts collection.
Keywords: France -- History, Military; Army officers, French